Distribution of nutrient constraints in Khasi mandarin (Citrus reticulata) orchards of Manipur (Current Horticulture, 2024)
The studies were carried out covering as many as 40 orchards of Khasi mandarin (Citrus reticulate Blanco) in Thangal village of sub-division Nungba under Tamenglong district during 2010-2011. Nutrient constraints in the form of N, P, Ca, Mg, Cu, and Zn were identified using these diagnostics which must find a due place in a fertilizer programme of mandarin orchards in the region to obtain sustainable optimum fruit yield. The values of available nutrients, viz. N, P, and K across 40 orchards varied from 92.2 to 348.2 mg/kg, 5.0 to 9.4 mg/kg, 110.0 to 440.1 mg/kg, respectively, with corresponding coefficient of variation of 11.8, 9.2, and 16.4% respectively. Soil micronutrients showed a large variation of 11.2- 48.1 mg/kg Fe (CV 16.2%), 11.4-44.0 mg/kg Mn (CV 11.2%), 0.80-2.5 mg/kg Cu (CV 6.9%) and 0.50-2.8 mg/kg Zn (CV 7.4%). Leaf nutrient concentration like soil fertility showed a wide variation from 1.62-2.62 % N, 0.04-0.12% P, 0.72-1.89% K, 0.90-2.24% Ca and 0.28-0.61% Mg. Similarly, micronutrients, Fe, Mn, Cu, and Zn varied from 118.4-282.3, 32.3-92.4, 1.0-3.8 and 14.6-28.4 ppm. These observations give an insight about the order in which, different nutrients are preferred by specific citrus cultivar, and the ratio in which different nutrients are removed. Such nutrient removal patterns are to be meted out in order to maintain the sustained supply of nutrients through soil.
Keywords: Khasi mandarin; Macro-micro nutrients status; Orchard; Nutrient removal